The Effects of Hemodynamic Unloading in African Americans Implanted with Left Ventricular Assist Devices. Issue 2 (February 2019) - Tehrani, David M.; Rodgers, Daniel; Adatya, Sirtaz; Sarswat, Nitasha; Raikhelkar, Jayant; Kim, Gene H.; Sayer, Gabriel; Uriel, Nir
Abstract : We aim to evaluate the echocardiographic/hemodynamic effects of left ventricular assist devices in African American (AA) versus non-AA patients undergoing ramp speed optimization and its subsequent effect on readmissions. In 65 patients (26 AA), no differences in baseline echocardiographic/hemodynamic parameters were noted. During ramp testing, there was a significantly greater increase in cardiac output (slope: 0.29 ± 0.24 vs . 0.15 ± 0.12, p < 0.01) with more rapid decrease in left ventricular end-diastolic diameter (slope: −0.21 ± 0.14 vs . −0.13 ± 0.07 L/min, p < 0.01) in the AA group. AAs had higher all-cause, but similar heart failure readmission rate as compared with the non-AA group.